Addressing healthcare for migrants and ethnic minorities in Europe: A review of training programmes. (February 2019) - Chiarenza, Antonio; Horvat, Lidia; Lanting, Katja; Ciannameo, Anna; Suurmond, Jeanine
Background: The global phenomenon of migration has dramatically changed the social context in which healthcare professionals operate. European states are facing a growing need to effectively train healthcare professionals to understand and respond appropriately to the diverse needs of migrants and ethnic minorities. While many European Union (EU) countries have adopted specific initiatives, there is considerable variation in these activities and few examples of evaluation of the quality of these training courses. Aims: This article describes findings from a review conducted as a part of the 'Training packages for health professionals to improve access and quality of health services for migrants and ethnic minorities, including the Roma (MEM-TP)' project, which sought to identify and assess training programmes for health professionals delivered in Europe between 2004 and 2013. Methods: The review and analysis of training materials comprised three components: (1) a review of the published and unpublished literature, (2) a survey addressing national contact persons, and representatives of international organisations and non-governmental organisations and (3) an assessment of the quality of the training programmes identified. Results: The review showed that training programmes tend to be characterised by low levels of participant involvement in training development, delivery and evaluation. Training programmes often lacked an explicit pedagogical approach, did not systematically focus on outcomes in training design, implementation and evaluation, and were poorly linked to key organisational and policy support. Finally, while cultural competence continues to be the broad conceptual approach used in training programmes, alternate approaches such as intersectionality, equity and person-centred care are emergent. Conclusion: Training programmes in Europe can be further improved in order to ensure an effective response to the diverse needs of patients, carers, health professionals and the community.